Marx, l’utopia, la transizione - Vaccaro, Giambattista (Bollettino Filosofico, 2025)
History of utopia shows that this notion points out the positive side of a transition program as a social imagination of a possible different and better society based on the criticism of the present one. This article reconstructs the position of Marx in this history through a recognition of the places in his works where he outlines the future society as a reign of freedom without alienation. This idea has been inherited by Western Marxism. Keywords: Alienation, Communism, Freedom, Marx, Utopia